2003
DOI: 10.1074/jbc.m309545200
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Dynamic Interactions between Phospholamban and the Canine Cardiac Ca2+ Pump Revealed with Use of Heterobifunctional Cross-linking Agents

Abstract: Heterobifunctional thiol to amine cross-linking agents were used to gain new insights on the dynamics and conformational factors governing the interaction between the cardiac Ca 2؉ pump (SERCA2a) and phospholamban (PLB). PLB is a small protein inhibitor of SERCA2a that reduces enzyme affinity for Ca 2؉ and thereby regulates cardiac contractility. We found that the PLB monomer with Asn 27 or Asn 30 changed to Cys (N27C-PLB or N30C-PLB) cross-linked to lysine of SERCA2a within seconds with >80% efficiency. Optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
148
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(168 citation statements)
references
References 42 publications
16
148
2
2
Order By: Relevance
“…Unfortunately, accurate measurement of Ca 2ϩ binding affinity with 45 Ca 2ϩ requires relatively high expression levels of the Ca 2ϩ -ATPase (13), which is difficult to achieve in recombinant systems (14). As an alternative, we have demonstrated that the Ca 2ϩ affinity of the enzyme is accurately estimated by assaying Ca 2ϩ inhibition of PLB cross-linking to SERCA2a (7,10). For example, N30C of PLB cross-links to Lys 328 of SERCA2a with the heterobifunctional cross-linker KMUS, and PLB cross-linking is inhibited by micromolar Ca 2ϩ concentration over the same concentration range (K i ϳ 0.3 M) as enzyme activation occurs (K Ca ϳ 0.3 M).…”
Section: ؉mentioning
confidence: 97%
See 4 more Smart Citations
“…Unfortunately, accurate measurement of Ca 2ϩ binding affinity with 45 Ca 2ϩ requires relatively high expression levels of the Ca 2ϩ -ATPase (13), which is difficult to achieve in recombinant systems (14). As an alternative, we have demonstrated that the Ca 2ϩ affinity of the enzyme is accurately estimated by assaying Ca 2ϩ inhibition of PLB cross-linking to SERCA2a (7,10). For example, N30C of PLB cross-links to Lys 328 of SERCA2a with the heterobifunctional cross-linker KMUS, and PLB cross-linking is inhibited by micromolar Ca 2ϩ concentration over the same concentration range (K i ϳ 0.3 M) as enzyme activation occurs (K Ca ϳ 0.3 M).…”
Section: ؉mentioning
confidence: 97%
“…For consistency with previous cross-linking studies, N30C-PLB was made on the Cys-less PLB background, in which Cys residues 36, 41, and 46 were mutated to Ala (7,10). N30C-PLB has been previously well characterized, and is fully functional with an inhibitory potency similar to wild-type PLB (7,10). In control experiments, ATPase activity by forming a dead-end complex with the enzyme in E2 (E2⅐TG) (18).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations